Literasi Menstruasi dan Pubertas pada Santriwati: Studi Tingkat Pengetahuan di Pondok Pesantren Jember - Ayu Hardiyanti, Setiya; Rahmawati, Pudji (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The lack of reproductive health literacy among adolescent girls, especially regarding menstruation and puberty, remains a common problem in Islamic boarding schools. Limited access to information and embarrassment in discussing reproductive health topics make female students prone to misunderstandings, anxiety, and improper hygiene practices. Therefore, community service activities were carried out with the aim of improving and determining the level of understanding of female students regarding menstruation and puberty as part of efforts to promote adolescent reproductive health in Islamic boarding schools. The community service method used was an educational activity with a descriptive quantitative approach through the distribution of a closed questionnaire consisting of 15 questions to 10 female students who had experienced menstruation. The results of the activity showed that the average level of knowledge of female students reached 81.0% and was in the high category, with the highest score of 88.9% and the lowest of 71.1%. These findings indicate that female students have a fairly good basic understanding of interpersonal understanding. This community service activity emphasizes the importance of continuous and structured reproductive health education in Islamic boarding schools to strengthen female students' readiness to face puberty and maintain optimal reproductive health.